Evaluation of athletic club training management fostered by youth and sports department, Aceh Province, Indonesia - Zikrur Rahmat; . Irfandi; Abdullah Al-Hazmy; Sapta Kunta Purnama; Agus Kristiyanto (Nicolaus Copernicus University in Toruń, 2018)
This study aims to evaluate the management of the athletic club, especially jump and throwing numbers under Youth and Sports Department of Aceh, and specifically aimed to assess the extent to which the development of the management of athletic sports clubs in each district/sub- district under the Youth and Sports Department of Aceh. This research is conducted in Sabang, Aceh Besar, Pidie Jaya, Bener Meriah, Gayo Lues, Aceh Jaya, Simeulue and Aceh Singkil. The method used is a qualitative research method, where only judging, see the feasibility of development management of athletic club management. The result of the research and discussion shows that the management process of an athletic club in Aceh is still minimal, this is because the management, recruitment process, and financing are still classified as less, still in the stage of revamping towards the more advanced.